Beliefs and practices in health care (2010)
The objective is to review the concepts of beliefs and practices of health care as cultural expressions in order to highlight to caregivers the necessary aspects for them to provide a culturally consistent care, a more human and effective one. From the conception of culture as a human creation which influences and shapes people's beliefs and practices, some definitions of the concepts as of social psicology, anthropology, sociology and transcultural nursing aspects are revised. We found that both beliefs and healthcare practices were originated and developed within the social context, they are mutually influenced and they are a part of the dynamic character which allows culture to favor the adaptation of a person to his/her environment. Taking into account cultural aspects, gives care a human touch and helps achieve therapeutic objectives. This conceptual revision is a product of the doctoral thesis "Beliefs and care practices of older people in a disability situation, in a context of poverty in Cartagena", which is worked on within the projects of the Cultural Health Care group, Nursing Faculty of the Colombia National University, Bogotá.